The Effect of E-Service Quality on Revisit Intention with Customer Satisfaction as a Mediation Variable for Car Buying and Selling Websites in Indonesia - Faradiba, Dimarta Julkha; Efrata, Tommy Christian (Universitas Ciputra Surabaya, 2023)
This research aims to investigate the effect of E-Service Quality on Revisit Intention with E-Customer Satisfaction and E-Trust as mediating variables on the websites for buying and selling used cars in Indonesia. The background of this research is the fluctuating conditions of the number of visits to the website for buying and selling used cars. The instability in the number of visitors occurs due to some factors in service quality. E-Service Quality, E-Trust, and E-Customer Satisfaction can have a significant impact on the company to increase traffic on each website. The method used in this research is a quantitative method using SEM-PLS with a data collection tool using a questionnaire with a semantic differential semantic scale and conducted in November 2022 – December 2022. The sample of this research is 252 active users of one of the websites for buying and selling used cars, which are calculated using the Hair method. The results of this research are that E-Service Quality has a significant positive effect on E-Customer Satisfaction, E-Service Quality has a significant positive effect on E-Trust, E-Service Quality has a significant positive effect on Revisit Intention, E-Trust has a significant positive effect on E-Customer Satisfaction, E-Customer Satisfaction does not mediate the effect of E-Service Quality on Revisit Intention, and E-Trust mediates the effect of E-Service Quality on Revisit Intention.